2021
DOI: 10.36401/jipo-21-14
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaw in Patients Treated Concurrently with Antiresorptive and Antiangiogenic Agents: Systematic Review and Meta-Analysis

Abstract: Introduction Medication-related osteonecrosis of the jaws (MRONJ) is a known adverse event related to the use of antiresorptive (AR) drugs. More recently, an association between antiangiogenic (AA) drugs and MRONJ has been suggested. This review aimed to investigate the overall prevalence and relative risk of MRONJ in patients treated concurrently with AA and AR agents in comparison with a single AA or AR drug. Methods A revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…With respect to risk factors, Zheng J et al and Otto S et al mention that part of the success of prevention is a correct anamnesis, since patients who are going to receive medications associated with the development of osteonecrosis should not present oral infectious processes and their oral health must be optimal. Evidence shows that dental care prior to starting treatment with bisphosphonates prevents the development of MRONJ (31) (32); information corroborated by Srivastava A et al, who emphasize that the treatment of dental caries, periodontal disease, and extraction of teeth infected or at risk of developing infection must be carried out at least 4 weeks before therapy with antiangiogenic and antiresorptive drugs (24) (34).…”
Section: Discussionmentioning
confidence: 99%

Medication-related osteonecrosis: Literature review

Idrovo Campoverde María Coralía,
Bacuilima Ñauta Erika Susana,
Pesántez Alvarado Juan Martín
et al. 2023
World J. Adv. Res. Rev.
“…With respect to risk factors, Zheng J et al and Otto S et al mention that part of the success of prevention is a correct anamnesis, since patients who are going to receive medications associated with the development of osteonecrosis should not present oral infectious processes and their oral health must be optimal. Evidence shows that dental care prior to starting treatment with bisphosphonates prevents the development of MRONJ (31) (32); information corroborated by Srivastava A et al, who emphasize that the treatment of dental caries, periodontal disease, and extraction of teeth infected or at risk of developing infection must be carried out at least 4 weeks before therapy with antiangiogenic and antiresorptive drugs (24) (34).…”
Section: Discussionmentioning
confidence: 99%

Medication-related osteonecrosis: Literature review

Idrovo Campoverde María Coralía,
Bacuilima Ñauta Erika Susana,
Pesántez Alvarado Juan Martín
et al. 2023
World J. Adv. Res. Rev.
“…While underutilization of BMAs can lead to serious SREs, overutilization has the potential for unnecessary adverse events (hypocalcemia, ONJ, atypical fractures, etc.) and financial toxicities [ 43 , 44 , 45 , 46 ]. Pre-implementation chart review in our study also showed inappropriate usage of BMAs in 41.5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there should be no history of radiation therapy ( Ruggiero et al, 2022 ). Recently, an association between antiangiogenic medication and MRONJ has been suggested ( Srivastava et al, 2021 ). Although Raloxifene, a selective estrogen receptor modulator has fewer side effects relative to other antiresorptives, MRONJ has also been reported in some patients on Raloxifene ( Bindakhil et al, 2021 ).…”
Section: Drug-induced Craniofacial Deformitymentioning
confidence: 99%